Correlation of histological marrow characteristics and intravoxel incoherent motion-derived parameters in benign and malignant hematological disorders. Issue 123 (February 2020) - Fan, Rong; Zhu, Hong; Niu, Jinliang; Li, Jianting; Zheng, Rong; Song, Xiaoli
Highlights: The blood volume fraction f was well correlated with the histological features of marrow in anemia. The blood volume fraction f was well correlated with the histological features of marrow in acute leukemia. f can show the difference of vascularity between benign and malignant marrow disease. Abstract: Purpose: To investigate the relationship between intravoxel incoherent motion (IVIM) parameters and histological parameters of vascularity and cellularity in marrow of hyperplasia disease and compare the difference between benign and malignant marrow disorders. Methods: From August 2016 to March 2017, 43 newly diagnosed patients were recruited, which included 15 anemia patients (benign hemopathy) and 28 patients with acute leukemia (AL) (malignant hemopathy). All patients underwent IVIM in the lumbar marrow and the D, D*, f values were measured. The microvessel density (MVD) and cellularity of marrow were calculated from the sample of iliac crest biopsy. Pearson correlation analysis was used to study the relationship between IVIM-derived and histology-derived parameters. We performed unpaired t test to analyze the differences of all parameters between AL and anemia. Result: The MVD was positively correlated with f in patients with AL, anemia and both of them ( r = 0.692, P < 0.001; r = 0.595, P = 0.019; r = 0.673, P < 0.001, respectively). But there was no correlation between D * and MVD in three groups. D was not related to bone marrow cellularity (BMC) in all groups. In addition, the f and MVD were higher in AL than anemia ( t = 3.546, P = 0.001; t = 6.695, P < 0.001, respectively). The BMC was significantly higher in AL than in anemia ( t = 3.330, P = 0.004), but D and D* value had no significant difference between the two groups. Conclusion: The blood volume fraction f was positively correlated with the histological features of marrow in hematological disorders, while f can show the difference of vascularity between benign and malignant marrow disease.